Eleanor McElwee and the Formation of IEEE PCS. (April 2015) - Malone, Edward A.
This article examines the historical professional project that created the Institute of Radio Engineers' Professional Group on Engineering Writing an Speech (IRE PGEWS)—now called the Institute of Electrical and Electronics Engineers' Professional Communication Society (IEEE PCS)—and recounts the group's early history in detail. It also traces the career and recovers the professional contributions of the main organizer of PGEWS: Eleanor M. McElwee (1924–2008). The formation of PGEWS in 1957 was an intraoccupational strategy of inclusionary usurpation by "publications people" seeking to elevate their status within the engineering profession rather than attempting to build a separate profession of technical communication.